Recommendations for quality assurance in multiparametric flow cytometry: first consensus of the Brazilian Group of Flow Cytometry (GBCFLUX) - Rodolfo P. Correia; Ana Carolina A. Bortolucci; Annelise C. W. Lopes; Alex F. Sandes; Ana Paula de Azambuja; Marta A. Viana; Maria M. Sales; Mihoko Yamamoto; Nydia S. Bacal (Sociedade Brasileira de Patologia Clínica, 2015)
ABSTRACT The Brazilian Group of Flow Cytometry (Grupo Brasileiro de Citometria de Fluxo [GBCFLUX]), founded on April 24, 2010, is composed of experts in flow cytometry (FC) area who have the common objective of contributing to technical and scientific advances in Brazilian clinical and research laboratories. Among GBCFLUX working groups, the Quality Control (QC) subcommittee is responsible for discussing data in the literature and contributes to the quality assurance of the pre-analytical, analytical and post-analytical process in FC. The QC subcommittee's actions began through meetings and lectures, in which data from the literature were reviewed and discussed with all participating members of the GBCFLUX. In a second step, it was decided to draw up a text of technical and scientific consensus recommendations, informative and educative, for dissemination to all FC working groups in Brazil. To this effect, a questionnaire with objective responses was designed and sent to 35 recognized Brazilian institutions, in order to evaluate the QC profile of these institutions. Thus, the QC technical-scientific recommendations, which will be described in this updating article, are intended to ensure the process quality, technical standardization, and reproducibility of results in FC.